Secondary metabolites isolated from Richardia brasiliensis Gomes (Rubiaceae) - Pinto,Danielle S. (2008)
The family Rubiaceae comprises around 637 genera and approximately 10,700 species, occurring essentially in tropical regions of Brazil. Richardia brasiliensis Gomes, known popularly as "poaia branca", is native to Brazil south region, used in folk medicine as anti-emetic and in the treatment of diabetes. This work reports the isolation and structural identification of a flavonoid glycoside, a triterpene, a coumarin and two benzoic acid derivatives, aiming at contributing to the chemotaxonomy of the genus Richardia, through a phytochemical study of Richardia brasiliensis. By means of this study the metabolites isorhamnetin-3-O-rutinoside, oleanolic acid, the coumarin scopoletin and p-hydroxy-benzoic and m-methoxy-p-hydroxy-benzoic acids were isolated and identified. All of them, but the latter, were isolated for the first time in the genus, thereby presenting relevant chemotaxonomic importance to it. The structures were identified using spectroscopic techniques such as IR, one and two-dimensional ¹H and 13C NMR besides comparison with literature data.